Men who sell sex : international perspectives on male prostitution and AIDS - Aggleton, Peter (Social aspects of AIDS., 1999)
Men Who Sell Sex is the first comprehensive international account of male prostitution and AIDS. While much is known about female prostitution and sex work, relatively little is known about men who sell sex - either to women or other men. This book brings together an authoritative collection of essays from different countries and examines sexual behaviour, the reasons men sell sex, the meanings involved, and implications for HIV prevention. The authors are all experts in their fields and individual chapters offer a compelling description of the reasons men sell sex and the pleasures and risks involved.